PENGARUH INTENSITAS LATIHAN DENGAN LAMA LATIHAN TERHADAP PENINGKATAN VO2 MAX - Syarkawi - (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2011)
One of the intention of doing activity of practice fisik/olahraga is constructive of prima is condition of physical. Is while determinant the core important is the level of oxygen volume Maximal (VO2 MAX) which can be consumed by body at the (time) of tiring and hard physical job/activity. To quicken it reaching of condition of this physical is needed by theX the practice program searching is most effective. During the time is two the practice program apply solidarity of practice intensity and the duration practice, that is the done with is intensity ( 70%-80%) with practice llama of 30 high level intensity and minute (90%-100% with practice llama of 15 minute. But which practice program which more effective to improvement VO2 MAX at someone, likely not yet can be determined. On the basis of the consideration of this research is done. Intention of this research is to know (1) Signifikansi influence of practice intensity of 70%-80% from ability MAX with practice of 30 minute to pengingkatan VO2 MAX, (2) Signifikansi influence of practice intensity of 90%-100% from ability MAXsimal with practice llama of 15 minute to improvement VO2 MAX, (3) Signifikansi difference of influence of practice intensity of 70%-80% from ability MAX with practice of 30 minute and practice intensity of 90%-100% from ability MAXsimal with practice of 15 minute to improvement VO2 MAX. Population in this research is generation student of 2009 study program Penjaskesrek STKIP Paris Barantai Kotabaru. Subyek taken as sampel amount to 42 student people and 90 population member people. Intake technique sampel Random Samplingly. Is while research method the used is experiment method by using research device Matched Subjects Design. Technique data collecting in this research use tes, that is with instrumentes aerobik (run 2, 40 km) from Cooper to collect the data VO2 MAX. Is while tes analysis to test the hypothesis is using the statistical analysis technique of tests comparability T. Pursuant to analysis result which have been done inferential; (1) Practice intensity of 70%-80% with practice llama of 30 minute have the influence signifikan to improvement VO2 MAX, (2) Practice intensity of 90%-100% with practice of 15 minute have the influence signifikan to improvement VO2 MAX, (3) There no difference of the influence signifikan among/between practice intensities of 70%-80% with practice of 30 minute and practice intensity of 90%-100% with practice of 15 minute to improvement VO2 MAX